STYLISTIC AND EXPRESSIVE FEATURES OF PHRASEOLOGICAL UNITS IN ENGLISH AND UZBEK SHORT STORIES - Nafisa Kubayeva, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article investigates the stylistic and expressive functions of phraseological units in English and Uzbek short stories. Phraseological expressions play a significant role in literary discourse because they enhance imagery, emotional intensity, and artistic individuality. The research focuses on the ways writers employ idioms, proverbs, and fixed expressions to shape characterization, create realism, and strengthen narrative expressiveness. Through comparative analysis, the study identifies both common and culture-specific stylistic features of phraseological units in English and Uzbek fiction. The article also examines the relationship between phraseology and national mentality, emphasizing the role of idiomatic language in reflecting social values, emotions, and cultural identity. The findings demonstrate that phraseological units are essential stylistic tools that enrich literary language and deepen the aesthetic impact of narrative texts.